Diverse perceptions among engineering students and staff of the enablers and constraints of academic resilience - Mapaling, C.; du Plooy, B.; Webb, P. (South African Journal of Higher Education, 2024)
High dropout rates and a lack of academic resilience continue to plague South African higher education. Often, this is more prevalent in practical disciplines that have been subjected to curriculum changes in recent years, such as engineering. It is challenging to understand academic resilience in university settings due to insufficient research. Therefore, more information is needed on the role of personal characteristics and the socio-ecological university environment in enabling and constraining students’ academic resilience. To assist higher education institutions in theorising academic resilience, this article presents a novel conceptual framework of Ungar’s social-ecological theory, and Ebersöhn’s Flocking theory. As part of this theorisation, this article also provides diverse perspectives on academic resilience from engineering students, lecturers, and support staff through semi-structured interviews. An analysis of this qualitative data was conducted using thematic analysis. A major finding of the study was that enabling factors were principally personal, whereas constraining factors were principally socio-ecological. Findings led to the development of an original framework for conceptualising the enablers and constraints of academic resilience in engineering students. This conceptual framework could guide towards the identification of areas of priority for academic resilience and in doing so contribute to interventions to reduce student dropout.